1998
DOI: 10.1177/026309239801700205
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Response to Sudden Load: A Tool to Evaluate Fatigue

Abstract: Sixteen subjects were exposed to fatiguing (vibration) and restorative (walking) interventions to assess their response to sudden loads. Unexpected loads, which people often experience, can lead to high forces in the spine and may be a cause of low irack injury. Erector spinae responses to sudden load were mediated by exposure to vibration and walking. Reaction time was affected by fatigue. Vertical vibration exposure significantly increased the muscle response time. Walking was able to ameliorate that effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
113
4
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 0 publications
3
113
4
4
Order By: Relevance
“…In the literature, experiments on sudden loading dynamics have delays in muscle response ranging from 127 to 205ms depending on the measurement method (Granata, Slota, & Wilson, 2004;Lavender, Marras, & Miller, 1993;Wilder et al, 1996). Two factors contribute to the slightly longer times observed in this study.…”
Section: Discussionmentioning
confidence: 69%
“…In the literature, experiments on sudden loading dynamics have delays in muscle response ranging from 127 to 205ms depending on the measurement method (Granata, Slota, & Wilson, 2004;Lavender, Marras, & Miller, 1993;Wilder et al, 1996). Two factors contribute to the slightly longer times observed in this study.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies employing loading perturbations have also documented alterations in neuromuscular control for subjects with LBP [18,32]. In response to horizontal support surface perturbations, subjects with chronic LBP [15], and episodic LBP [11] have been found to demonstrate a decrease in the magnitude of center of mass displacement and a delayed onset of net center of pressure displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Three general aspects of altered muscle recruitment patterns in people with back pain have been investigated: (1) altered muscle activation patterns, especially coactivation, in a static task such as pulling against a fixed object or slow lifting [1,3,19,20,28], (2) altered muscle reflex latency times in response to a sudden perturbation [26] or dropped weight [18,32], quick release of trunk loading [27], or moving support platform [10], (3) altered muscle activation pattern in anticipation of an unexpected or voluntary perturbation [14,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
IntroductionRecent studies of whole body vibration in seated postures have suggested that the neuromotor system may play a role in the etiology of low back disorders [1][2][3][4] . A number of researchers have modeled whole body vibration transmission to the low back, spine and head 5 .
…”
mentioning
confidence: 99%